Desenvolvimento de sensor bioletroquímico para detecção da hanseníase - Afonso, André Santiago (2008)
Leprosy is a chronic, granulomatous and dermatological disease, from infection caused by the bacillus Mycobacterium leprae. It is object of intervention of the state, because when untreated cause disability in the economically active population. Brazil remains one of the four endemic countries responsible for 34% of all cases registered at the beginning of 2007. The disease diagnosis can only be done after the onset of disease symptoms. Prophylactic measures are possible when using techniques such as ELISA and PCR, which can be performed only in specialized laboratories, not considering the needs of the endemic countries. Such problems can be circumvented by using tools of low cost, simple and sensitive handling as biosensors. In this work, poly(4-aminophenol) matrix, was used for immobilization and detection of specific PCR product for Hansen bacillus. The surface modification with the film was confirmed observing the electrochemical differences of the electrode without modification front at redox pair Fe2+/Fe3+ and supported electrolyte. The characterization of the polymeric matrix was carried out by FTIR, electrochemical impedance spectroscopy, electrochemical quartz crystal microbalance and studies of thermal stability. The FTIR data indicate polymerization possible by C-N-C bonds. The stability of the film at 98 ° C was measured and even showed 60% of its electroative properties after twenty minutes of heat treatment. being, therefore, adequate for the used methodology, in this work, for biomolecules immobilization. The detection of nitrogenated bases on the new matrix was possible in pH 4.5 and 7.4. The eletrolite, phosphate buffer in pH 7.4, was the most adequate to nitrogenated bases detection and in turn, for PCR products. This electrolyte was used for immobilization of the denaturated PCR product (RLEP3), contained 78pb, and specific for the Hansen bacillus. The DNA fragment immobilization was confirmed monitoring the oxidation peaks of guanosine monophosphate and adenosine monophosphate and also by means of electrochemical impedance spectroscopy studies. Hybridization indicator, ferrocenecarboxyaldehyde and methylene blue, had been used to differentiate complementary or not complementary target. With the hibridization occurrence, a reduction in the current signal values was observed, for both indicators, monitoring the indicator. The small detection limit, 10-10 mol.L-1, of the complementary target, was reached using methylene blue as indicator. When the probe was submitted to not complementary target, it was not observed change in the current values of immobilized probe. At the end of thirty days the biosensor kept 60% of their electrochemical properties These studies demonstrated the viability of constructing of an electrochemical biosensor using eletroactive indicators of low-cost, which can be used in real samples with the DNA of Hansen bacillus. For the first time, in the open literature, it was demonstred the modified electrodes production with poly(4-aminophenol) as matrix to immobilization and detection of specific PCRproduct to leprosy detection.